Evaluation of ignitable liquid residue adsorption on multiple activated carbon devices for forensic fire debris analysis - Rahman, Syamilah Abdul (2023)
Fire investigations play a pivotal role in uncovering the causes and origins of fire incidents, vital for the administration of justice and fire prevention. Central to these investigations is the analysis of fire debris, which involves detecting and identifying ignitable liquid residues (ILRs). Current practices employ various methods for ILR collection, including sterile cotton swabs and activated carbon strips. However, these methods present limitations, such as incomplete ILR recovery and high acquisition costs. This study addresses these challenges by comprehensively evaluating multiple activated carbon (AC) devices as potential alternatives for ILR adsorption. Several factors such as sampling time and sampling surface were manipulated to assess the performance of the AC devices. By doing so, it aims to identify the most efficient and cost-effective AC device for ILR collection, contributing to the enhancement of forensic fire debris analysis. Among the evaluated AC devices, AC cloth stands out due to its remarkable performance. Physical characterization revealed that AC cloth possesses the highest surface area, which results in an exceptional adsorption capacity. Furthermore, GC-MS analysis demonstrated its remarkable efficacy in ILR adsorption, particularly on porous surfaces like wood. Additionally, the results of GC-MS analysis highlighted AC cloth's consistent ability to adsorb volatile organic compounds (VOCs) of gasoline across various sampling durations, ranging from 0.5 to 48 hours. These findings underscore AC cloth as a promising candidate for ILR adsorption in forensic fire debris analysis, offering high surface area and versatility across different sampling conditions.